The reaction of the WSE to U.S. employment news announcements - Suliga, Milena; Wójtowicz, Tomasz (Managerial Economics, 2014)
Stock markets react to various information. One of the most important information concerns macroeconomic data because it describes the state of the economy. The U.S. is the world’s largest economy and thus American macroeconomic news announcements strongly affects European stock markets. In this paper we investigate the reaction of stock prices on the Warsaw Stock Exchange to values of macroeconomic indicators published in the Employment Report by the U.S. Bureau of Labor Statistics. We study the impact of macroeconomic indicators separately as well as interrelations between them. It allows us to specify which of the indicators under study is the most informative. We analyze the impact of information about the state of the labor market in the U.S. in the period from January 2004 to November 2012. In order to describe duration, direction and significance of the impact we apply the event study analysis to intraday returns of WIG – the main index of WSE.